Edukasi Mual dan Muntah Pasca Operasi terhadap Pengetahuan Orang Tua dan Dehidrasi Anak - Feri, Jhon; Juartika, Wella; Oktaviani, Eva (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the effect of education about postoperative nausea and vomiting on increasing parental knowledge and reducing the incidence of dehydration in children. The research method used was a quasi-experimental design with a pretest-posttest approach with a control group. The results showed a significant increase in parental knowledge about nausea and vomiting management in the intervention group compared to the control group (p < 0.05). In conclusion, the practical implications of this study are significant. Education about postoperative nausea and vomiting effectively increases parental knowledge and reduces the incidence of dehydration in children. The education program, which is routinely applied to pediatric patients undergoing surgery, demonstrates its potential to improve the quality of care and reduce postoperative complications. Keywords: Children, Dehydration, Education, Postoperative Nausea and Vomiting, Parental Knowledge